(untitled) (International journal of artificial intelligence, 2024)
In this study we investigate how artificial intelligence (AI) can transform the human resource management (HRM) functions in the banking sector exploring the use of AI within three key areas: talent acquisition, employee engagement and performance evaluation. In this highly competitive, regulated banking environment, the use of AI driven tools deliver impactful improvements, both during the hiring process by improving predictive analytics to identify top talent as well as robust automated compliance checks and the subsequent development of sentiment analysis to assist with tracking employee satisfaction. The research talks about how these technologies help solve sector specific challenges — for example, automating recruitment processes for highly specialised roles, or implementing fairness in employee appraisals within highly prescriptive operating frameworks relevant to banks. Further, it looks at the ethical and operational facets of adopting AI, and how this could hold implications for ethics and how transparency of AI algorithmic decision making is required to maintain the trust of a very focused and scrutinized marketplace. The study adopts a mixed method approach integrating quantitative surveys conducted among banking HR professionals with qualitative case studies of the leading financial institutions to understand a nuanced picture of AI adoption. It critically investigates how in the face of emergent digital banking requirements, AI applications can enable workforce adaptability and skill development. Think of the story of Machine learning algorithms able to spot skill gaps and suggest customized training programs to keep people nimble in the crooked face of technological disruptions. In this regard, the research also discusses the specific context of the banking sector in Uzbekistan, and suggests suitable AI-based HR strategies for local application in accordance with industry regulatory and cultural requirements. Through taking them actionable research, the study emphasizes AI’s potential to help HRM in banks improve operational efficiency, increase employee satisfaction and improve the bank’s future ready workforce.